ANALYSIS OF COMPANY CHARACTERISTICS AND OWNERSHIP STRUCTURE OF DIVIDEND POLICY IN INDONESIA WITH FREE CASH FLOW AS MODERATING VARIABLE - Husaini, Husaini; Nurlela, Nurlela; Marzuki, Marzuki; Ulfa Zahra; Rahma Ziana Safitri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study examines the effect of ownership structure and company characteristics on dividend policy in companies listed on the Indonesia Stock Exchange with an observation period from 2015-2020. This study also interacts with the Free Cash Flow (FCF) variable with other company characteristic variables. The population in this research is all companies that pay dividends. Sampling method using purposive sampling. The variables used to test the dividend policy are managerial ownership, institutional ownership, profitability, leverage, investment opportunity set (IOS) and free cash flows (FCF). Processing and analysis of data using panel data regression with the help of E-Views software. In selecting the model, the Chow and Housman tests were first carried out. After that, the right model will be obtained to provide solutions to the problems in this study. The results of this study found that before the MRA test was carried out, the variables that significantly influenced dividend policy were Managerial Ownership and Free Cash Flow, while the Leverage, Institutional Ownership and IOS variables had no significant effect. After testing the variable MRA that is able to moderate the influence on dividend policy, namely Leverage peroxided by DER. This means that debt has no impact on dividend policy as long as there is enough FCF available to meet debt interest. While other variables are not significantly moderated by FCF.